Anticoagulant therapy in catheter ablation of atrial fibrillation and flutter - M. V. Serova; D. A. Andreev; M. I. Chashkina; Z. K. Salpagarova (Кардиоваскулярная терапия и профилактика)
Catheter ablation (CA) of atrial fibrillation and flutter is associated with a high risk of both perioperative thromboembolic events and bleeding. Adequate anticoagulation is imperative to reduce the risk of complications. The aim of this review was to analyze modern approaches to anticoagulant therapy for CA of atrial fibrillation and flutter, as well as provide practical information based on a comparison of current guidelines and evidence base. The search for literature sources on anticoagulant therapy in CA was carried out in the PubMed, Scopus, Web of Science databases. The results of key randomized trials and meta-analyzes are presented, and a comparison of current Russian and international guidelines is given. Unresolved issues requiring further research are discussed.